Improved Agreement between Experienced and Inexperienced Observers using a Standardized Evaluation Protocol for Cardiac Volumetry and Infarct Size Measurement - Groth, M.; Muellerleile, K.; Klink, T.; Säring, D.; Halaj, S.; Folwarski, G.; Kaul, M.; Bannas, P.; Adam, G.; Lund, G. K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To study the agreement between experienced and inexperienced observers before and after training using a standardized evaluation protocol for cardiac magnetic resonance imaging (CMR) measurements of left ventricular (LV) volumes, mass and infarct size. Materials and Methods: First, 10 CMR studies from patients with myocardial infarction were analyzed by 2 experienced and 4 inexperienced observers in respect to end-diastolic volume (EDV), end-systolic volume (ESV), ejection fraction (EF), LV mass and infarct size. Subsequently, the inexperienced observers were trained using a standardized evaluation protocol. Thereafter, all observers analyzed another 10 CMR studies. Results: Before training the relative difference between experienced and inexperienced observers was –4.3 ± 8.2 % for EDV, –13.3 ± 14.2 % for ESV, 5.9 ± 8.2 % for EF, –12.2 ± 10.9 % for LV mass and –27.0 ± 29.0 % for infarct size in gram. After training, agreement significantly improved to 0.2 ± 8.8 % for EDV (p < 0.05), –2.1 ± 10.9 for ESV (p < 0.01), 1.5 ± 6.9 % for EF (p < 0.05), and –3.6 ± 17.1 % for infarct size (p < 0.0001), but no improvement was seen for LV mass (–11.2 ± 7.9, p = 0.64). A slice based analysis showed, that the variable inclusion of the most basal and apical slices were mainly responsible for the low agreement of the measurements before training.Conclusion: Training using a standardized evaluation protocol significantly improved the agreement between experienced and inexperienced observers for important CMR parameters. The proposed evaluation protocol can be used for training to improve the reproducibility of CMR measurements.
Keywords: cardiac; MR-imaging; ischemia/infarction